Multi-Channel Sparse-Frequency-Scanning White-Light Interferometry with Adaptive Mode Locking for Pulse Wave Velocity Measurement - Yifei Xu; Laiben Gao; Cheng Qian; Yiping Wang; Wenyan Liu; Xiaoyan Cai; Qiang Liu (Photonics)
Fiber-optic Fabry–Pérot (F–P) sensors offer significant potential for non-invasive hemodynamic monitoring, but existing sensing systems face limitations in multi-channel measurement capabilities and dynamic demodulation accuracy. This study introduces a sparse-frequency-scanning white-light interferometry (SFS-WLI) system with an adaptive mode-locked cross-correlation (MLCC) algorithm to address these challenges. The system leverages telecom-grade semiconductor lasers (191.2–196.15 THz sweep range, 50 GHz step) and a Fibonacci-optimized MLCC algorithm to achieve real-time cavity length demodulation at 5 kHz. Compared to normal MLCC algorithm, the Fibonacci-optimized algorithm reduces the number of computational iterations by 57 times while maintaining sub-nanometer resolution under dynamic perturbations. Experimental validation demonstrated a carotid–radial pulse wave velocity of 5.12 m/s in a healthy male volunteer. This work provides a scalable and cost-effective solution for cardiovascular monitoring with potential applications in point-of-care testing (POCT) and telemedicine.